2014
DOI: 10.1007/s10877-014-9573-7
|View full text |Cite
|
Sign up to set email alerts
|

An optimal frequency range for assessing the pressure reactivity index in patients with traumatic brain injury

Abstract: The objective of this study was to identify the optimal frequency range for computing the pressure reactivity index (PRx). PRx is a clinical method for assessing cerebral pressure autoregulation based on the correlation of spontaneous variations of arterial blood pressure (ABP) and intracranial pressure (ICP). Our hypothesis was that optimizing the methodology for computing PRx in this way could produce a more stable, reliable and clinically useful index of autoregulation status. The patients studied were a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 31 publications
1
60
0
Order By: Relevance
“…AMP was determined by calculating the fundamental Fourier amplitude of the ICP pulse waveforms over a 10 s window, updated every 10 s. Ten-second moving averages (updated every 10 s to avoid data overlap) were calculated for all recorded signals: ICP, ABP (which produced MAP), AMP, and CPP. This 10-s moving average filter is applied to the raw signals so as to decimate signal frequency into the range appropriate for vasogenic slow-wave evaluation (i.e., 0.05 to 0.005 Hz) [ 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AMP was determined by calculating the fundamental Fourier amplitude of the ICP pulse waveforms over a 10 s window, updated every 10 s. Ten-second moving averages (updated every 10 s to avoid data overlap) were calculated for all recorded signals: ICP, ABP (which produced MAP), AMP, and CPP. This 10-s moving average filter is applied to the raw signals so as to decimate signal frequency into the range appropriate for vasogenic slow-wave evaluation (i.e., 0.05 to 0.005 Hz) [ 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Continuous indices of cerebrovascular reactivity were derived via the moving correlation coefficient between 30 consecutive 10 s mean windows (i.e., vasogenic slow-wave fluctuations) of the parent signals, updated every minute. PRx was derived via the correlation between slow-wave fluctuations (i.e., 0.05 to 0.005 Hz) in ICP and MAP [ 7 , 11 , 12 ]. PAx was derived via the correlation between slow-wave fluctuations in AMP and MAP.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study found that the pressure reactivity index was best evaluated in the frequency range with oscillations with periods from 55 to 15 s (PRx55-15) [5,12]. Similarly, ICP AMP 55-15 was an independent predictor of outcome, but ICPV-30m was a slightly stronger outcome predictor (Table 3).…”
Section: Icpv: Different Time Intervals and Relation To Outcomementioning
confidence: 87%
“…PRx, which originally was described by Czosnyka et al, was calculated as a moving 5-min correlation of 10 s averages of ICP and MAP [11]. We also used a variant of PRx, PRx55-15, that was calculated in a similar way as PRx, but with a bandpass filter limiting the analysis to oscillations with periods from 55 to 15 s [5,12].…”
Section: Physiological Analysismentioning
confidence: 99%
“…In the current study we have used the methodology described by Howells et al. ( 27 ), which uses a filter with a bandpass of 0.018–0.07 Hz. Thus, we limit the correlation analysis to oscillations of MAP and ICP with periods of 15 to 55 seconds in duration.…”
Section: Methodsmentioning
confidence: 99%